Paradox of Prevention: Determinants of Non-Communicable Disease Service Utilization Among Industrial Workers in Indonesia Using the Health Belief Model - Nasrul Zaman (Open Access Research Journal of Science and Technology, 2026)
The underutilization of Non-Communicable Disease (NCD) Integrated Health Services Program (IHSP) among industrial workers is a significant issue, primarily driven by internal factors such as limited awareness, perceived barriers, and cultural attitudes towards health. Workers often prioritize their work over personal health, leading to neglect of health services like NCD IHSP. This study aims to identify the internal factors influencing industrial workers’ utilization of NCD IHSP, applying the Health Belief Model (HBM) to assess perceived vulnerability, seriousness, benefits, barriers, and self-efficacy. The objective is to provide recommendations for improving service utilization at governmental and corporate levels. A quantitative approach using a structured questionnaire was conducted among 700 workers in ten industrial estates across Indonesia. Structural Equation Modeling (SEM) with SmartPLS was used to analyze the relationships between HBM variables and NCD IHSP utilization. The findings reveal that perceived seriousness and barriers significantly impact NCD IHSP utilization, whereas perceived benefits and self-efficacy show weaker associations. Many workers remain unaware of their NCD risks and do not utilize available preventive health screening services. The lack of targeted health campaigns and flexible worker service hours further contributes to low service uptake. The study concludes that increasing NCD IHSP utilization can be achieved through health education campaigns tailored to workers’ needs and environments. Raising awareness about NCD risks and emphasizing the benefits of early detection, integrated into workplace policies, is crucial for promoting healthy behaviours and reducing NCD risks among workers.